The MILESTONES modeling framework: An integrated analysis of national bioenergy strategies and their global environmental impacts. (December 2016) - Thrän, Daniela; Schaldach, Rüdiger; Millinger, Markus; Wolf, Verena; Arendt, Oliver; Ponitka, Jens; Gärtner, Sven; Rettenmaier, Nils; Hennenberg, Klaus; Schüngel, Jan
Abstract: Bioenergy policies affect both the environment and biomass availability for food, feed, and fiber on a national and international scale. To support policy makers, knowledge and methods from different scientific disciplines in the form of integrated assessments is necessary. Therefore we developed the MILESTONES framework which models the links between the national bioenergy system and the global land-use system as an integrated modeling approach. It builds on a set of three well-tested models (MAGNET, LandSHIFT and BENSIM). The prototype's functionality was demonstrated by assessing the environmental impacts of future German bioenergy strategies on a global level and along the entire biomass provision chain. The results from the case study show that, on the one hand, German bioenergy strategies have little effect on international market prices, but on the other hand land-use policies on an international level strongly influence the environmental performance of any German bioenergy strategy. Highlights: Integrated assessment of the global effects of German bioenergy strategies. Combination of national energy system, global trade and land-use models. Biofuels from food crops tend to be more cost-competitive than when they are from wood. The impact of Germany's bioenergy use is most sensitive to international land-use policies.